Rhythmic and interval‐based temporal orienting in autism. Issue 4 (12th January 2023) - Cannon, Jonathan; Eldracher, Emelie; Cardinaux, Annie; Irfan, Fatima; Bungert, Lindsay; Li, Cindy; O'Brien, Amanda; Treves, Isaac; Diamond, Sidney; Sinha, Pawan
Abstract: Individuals with autism spectrum disorder (ASD) may show secondary sensory and cognitive characteristics, including differences in auditory processing, attention, and, according to a prominent hypothesis, the formulation and utilization of predictions. We explored the overlap of audition, attention, and prediction with an online auditory "temporal orienting" task in which participants utilized predictive timing cues (both rhythmic and interval‐based) to improve their detection of faint sounds. We compared an autistic ( n  = 78) with a nonautistic ( n  = 83) group, controlling for nonverbal IQ, and used signal detection measures and reaction times to evaluate the effect of valid temporally predictive cues. We hypothesized that temporal orienting would be compromised in autism, but this was not supported by the data: the boost in performance induced by predictability was practically identical for the two groups, except for the small subset of the ASD group with co‐occurring attention deficit hyperactivity disorder, who received less benefit from interval‐based cueing. However, we found that the presence of a rhythm induced a significantly stronger bias toward reporting target detections in the ASD group at large, suggesting weakened response inhibition during rhythmic entrainment. Lay Summary: When we can predict the moment something important will likely happen, we can focus our attention on that moment in time to perceive it more accurately and respond to it faster. This process of "temporal orienting" plays an important role in social interaction and other day‐to‐day functioning. Based on previous literature, we hypothesized that temporal orienting would be less effective in autism, but our experiments indicated no difference in temporal orienting between autistic and nonautistic groups.